Rytietiškoji XVII a. lietuvių raštų kalba, jos kilmė ir išnykimas - Zinkevičius, Zigmas (Baltistica, 1972)
THE SEVENTEENTH CENTURY EAST LITHUANIAN LITERARY LANGUAGE, ITS RISE AND DISAPPEARANCE The Old Lithuanian literary records of the 16th and 17th centuries indicate the existence of three variants of literary Lithuanian at that time. An early literary variant based on the local West High Lithuanian dialect arose on the territory of Eastern Prussia (now the Kaliningrad District). Two literary languages developed on the territory of the Great Dukedom of Lithuania – Central Lithuanian (on the basis of the dialect of Kėdainiai environs) and Eastern Lithuanian. The purpose of this paper is to investigate the origin and fate of literary Eastern Lithuanian. A short characteristic of Eastern Lithuanian and a review of some attempts to establish its dialect background are followed by a detailed analysis of specific Eastern Lithuanian features and a conclusion is drawn that the town koine of Vilnius – the capital of the Great Dukedom of Lithuania served the basis for the formation of literary Eastern Lithuanian. The following features are of importance in accepting Vilnius as the centre of literary Eastern Lithuanian: the presence of ō in all positions, peculiar to the environs of Vilnius and quite alien to many present-day Eastern Lithuanian dialects, which have preserved an older pronunciation (ā or ā̊) esp. in unstressed positions; the presence of doublet forms with tautosyllabic combinations of the an type, indicating the proximity of the literary record to the an‖un isophone, which actually ran about 10–15 kilometres to the South-West of Vilnius; the presence of sporadic cases of the Dzūkai change of t, d into c, dz; its isophone ran to the East of Vilnius; the presence of pronoun forms of three types. 1) Nom. Sg. fern, tó (= present-day tà), 2) the same case form tój, 3) Nom. PI. masc. tíej, Instr. Sg. mase. túoj, fem. tą́j > tų́j (= present-day literary tiẽ, tuõ, tà); the contact area of these forms is just the environs of Vilnius; the presence of the 3rd pers. present tense forms without the ending -i (mýl side by side with mýli); sporadic monophthongization of ai, ei into a, e in kaĩp, teĩp, šiaĩp; sporadic spelling ey for the diphthong ai, indicating the weakened („Eastern Lithuanian”) pronunciation of the first component of the diphthong, typical of the dialects to the North of Vilnius. There are also other numerous linguo-geographical factors, supporting the above-mentioned localization of literary Eastern Lithuanian. On the other hand, no data contradicting such a hypothesis have been found in the literary records. In the paper the rise of the literary language on the basis of the Vilnius koine is substantiated by historical arguments as well; resp. a complicated linguistic situation of the 14th–16th centuries in the Great Dukedom of Lithuania is subjected to an analysis. The importance of the literary language under investigation for the entire Lithuanian linguistic culture is established. On the basis of the dialectological analysis of the written records of later centuries a conclusion is drawn that literary East Lithuanian ceased to exist early in the 18th century in connection with the increased Polonization of the Lithuanian town aristocracy.